A unified framework for 3D building surface reconstruction from fused LiDAR and photogrammetric data - Wahyu Marta Mutiarasari; Muhammad Zulkarnain Abd Rahman; Alias Abdul Rahman; Gurcan Buyuksalih (Applied Geomatics, 2026)
Reliable three-dimensional (3D) building surface reconstruction depends on accurate and comprehensive spatial data; however, acquiring such data remains challenging, particularly for point clouds. Data collected using terrestrial laser scanning (TLS) and unmanned aerial vehicle (UAV)-based LiDAR provide detailed geometric information but are often affected by occlusions, limited viewpoints, and sensor constraints, resulting in incomplete datasets. Although data fusion using the iterative closest point (ICP) algorithm and Laplacian-based enhancement can mitigate these limitations, existing research typically treats fusion and surface reconstruction as separate processes, often applying reconstruction directly to fused data without prior quality assessment. This limits the generation of complete and geometrically consistent 3D building models from heterogeneous datasets. To address this gap, this study proposes a unified framework for 3D building surface reconstruction from fused point clouds derived from TLS, UAV LiDAR, and photogrammetric sources. The workflow applies ICP for alignment, Laplacian-based enhancement for gap reduction, and quantitative evaluation of the enhanced point cloud prior to reconstruction using the Marching Cubes algorithm. The results show an average completeness of 86.9%, with the standard deviation improving from 0.173 m to 0.157 m (roof) and from 0.238 m to 0.191 m (wall). The reconstructed model satisfies level of detail 2 (LoD2) requirements. Although certain architectural features, such as windows and pillars, are preserved, they are not yet semantically structured, indicating potential for extension toward higher LoDs (e.g., LoD3). Overall, the framework highlights the importance of pre-reconstruction enhancement and evaluation and demonstrates its potential for supporting more complete and geometrically consistent 3D building modelling.

Enhancing village-level spatial planning with unmanned aerial vehicles: A comparative study of direct georeferencing and ground control points - Gunawan Setyo Prabowo; Suprapedi Suprapedi; Muhammad Bisri; Wayan Firdaus Mahmudy; Ari Sugeng Budiyanta; Nur Sugi; Try Kusuma Wardana; Aries Asrianto Ramadian; Hartono Hartono; Rudi Choirul Anwar; Unggul Satrio Yudhotomo (Applied Geomatics, 2026)

Automated geolocalization of vehicles from UAV footage: evaluating measurement precision of object detection and segmentation methods - Muhammad Waqas Ahmed; Muhammad Adnan; Muhammad Ahmed; Davy Janssens; Geert Wets; Afzal Ahmed; Wim Ectors (Applied Geomatics, 2026)

Advancing future drought characterization: a two-phase Bayesian model averaging approach for GCM ensemble calibration - Nosheen Amjad; Muhammad Ismail; Zulfiqar Ali (Applied Geomatics, 2026)

Assessing Meghna Riverbank dynamics and morphological changes in Bangladesh using geospatial techniques - Masuda Sultana; Muhammad Al-Amin Hoque; Biswajeet Pradhan (Applied Geomatics, 2025)

Interphase modeling of sedimentation rate using the GIS-based modified universal soil loss equation - Azmeri; Muhammad Iqbal; Muhammad Fauzi; Maimun Rizalihadi (Applied Geomatics, 2024)

The spatial–temporal variability of chlorophyll-a across the eastern Indonesian seas region using sentinel-3 OLCI - Eko Yuli Handoko; Muhammad Aldila Syariz; Noorlaila Hayati; Megivareza Putri; Mukhammad Muryono; Chung-Yen Kuo (Applied Geomatics, 2024)

Assessing the accuracy of open-source digital elevation models for the geomorphological analysis of very small islands of Indonesia - Bachtiar W. Mutaqin; Muhammad Nadafa Isnain; Muh Aris Marfai; Hendy Fatchurohman; Adolfo Quesada-Román; Nurul Khakhim (Applied Geomatics, 2023)

Spatio-temporal analysis of river channel pattern in lower course of River Ravi using GIS and remote sensing - Noor-ul Huda; Shakeel Mahmood; Rida Sajjid; Muhammad Irfan Ahamad (Applied Geomatics, 2023)

Geospatial analysis of desertification vulnerability using Mediterranean desertification and land use (MEDALUS) model in Kebbi State, Nigeria - Muhammad Mansur Aliero; Mohd Hasmadi Ismail; Mohamad Azani Alias; Alias Mohd Sood (Applied Geomatics, 2021)

Towards a Web GIS-based approach for mapping a dengue outbreak - Muhammad A. Butt; A. Khalid; A. Ali; S. A. Mahmood; J. Sami; J. Qureshi; K. Waheed; A. Khalid (Applied Geomatics, 2020)

Identification of archeological sites threatened with obliteration using space-borne and ground penetrating radars data in site of Tulul al-Ukhaidir, Iraq - Zaidoon Taha Abdulrazzaq; Jassim Muhammad Thabit; Ammar Jasim Al-Khafaji (Applied Geomatics, 2019)

Local-scale accuracy assessment of vegetation cover change maps derived from Global Forest Change data, ClasLite, and supervised classifications: case study at part of Riau Province, Indonesia - Sanjiwana Arjasakusuma; Muhammad Kamal; Muhammad Hafizt; Hernandea Frieda Forestriko (Applied Geomatics, 2018)

GeoWebEX: an open-source online system for synchronous collaboration on geographic information - Muhammad A. Butt; Syed Amer Mahmood; Syed Muhammad Hassan Raza (Applied Geomatics, 2018)

Towards Co-PPGIS—a collaborative public participatory GIS-based measure for transparency in housing schemes: a case of Lahore, Pakistan - Muhammad A. Butt; Songnian Li; Nasir Javed (Applied Geomatics, 2016)

UML-based requirement modeling of Web online synchronous collaborative public participatory GIS - Muhammad A. Butt; Songnian Li (Applied Geomatics, 2015)

Usability evaluation of collaborative PPGIS-GeoCWMI for supporting public participation during municipal planning and management services - Muhammad A. Butt; Songnian Li (Applied Geomatics, 2015)

Developing a web-based, collaborative PPGIS prototype to support public participation - Muhammad A. Butt; Songnian Li (Applied Geomatics, 2012)

Vertical gravity anomaly gradient effect of innermost zone on geoid-quasigeoid separation and an optimal integration radius in planar approximation - Sadiq Muhammad; Ahmad Zulfiqar; Ayub Muhammad (Applied Geomatics, 2010)